Pattern of healthcare resource utilization and direct costs associated with manic episodes in Spain - Tafalla, Monica (BioMed Central, 2010)
BACKGROUND: Although some studies indicate that bipolar disorder causes high health care resources consumption, no study is available addressing a cost estimation of bipolar disorder in Spain. The aim of this observational study was to evaluate healthcare resource utilization and the associated direct cost in patients with manic episodes in the Spanish setting. METHODS: Retrospective descriptive study was carried out in a consecutive sample of patients with a DSM-IV diagnosis of bipolar type I disorder with or without psychotic symptoms, aged 18 years or older, and who were having an active manic episode at the time of inclusion. Information regarding the current manic episode was collected retrospectively from the medical record and patient interview. RESULTS: Seven hundred and eighty-four evaluable patients, recruited by 182 psychiatrists, were included in the study. The direct cost associated with healthcare resource utilization during the manic episode was high, with a mean cost of nearly €4,500 per patient, of which approximately 55% corresponded to the cost of hospitalization, 30% to the cost of psychopharmacological treatment and 10% to the cost of specialized care. CONCLUSIONS: Our results show the high cost of management of the patient with a manic episode, which is mainly due to hospitalizations. In this regard, any intervention on the management of the manic patient that could reduce the need for hospitalization would have a significant impact on the costs of the disease.